2002
DOI: 10.1002/rcm.854
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline‐coated nanoelectrospray emitters: performance characteristics in the negative ion mode

Abstract: The increasing tendency to miniaturize analytical techniques has resulted in the widespread use of nanoelectrospray ionization mass spectrometry. A new polyaniline-coated nanoelectrospray emitter has shown increasing promise as a more durable and stable alternative to traditional metal-coated emitters. In this report, the utility of polyaniline-coated nanoelectrospray emitters in the negative ion mode is investigated. Here, oligonucleotides and peptides have been ionized in the negative mode using polyaniline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Negative mode ESI was first applied considering the charge status of the UA, but a stable spray was not achieved as is common in negative mode nanospray [24,32]. Upon applying positive ESI mode, however, high sensitivity detection with a well-defined peak was achieved.…”
Section: Ce/ms Using the Devised Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Negative mode ESI was first applied considering the charge status of the UA, but a stable spray was not achieved as is common in negative mode nanospray [24,32]. Upon applying positive ESI mode, however, high sensitivity detection with a well-defined peak was achieved.…”
Section: Ce/ms Using the Devised Interfacementioning
confidence: 99%
“…Initially, the surrounding area of the emitter tip was coated with an electrically conducting material such as silver [19], graphite [20], carbon [21] or gold [22]. An electro-conducting polymer such as polyaniline was even applied [23,24]. In general, however, electrical discharges at the emitter tip often damage the coating, which shortens the lifetime of the electrical contact to less than a few days.…”
Section: Introductionmentioning
confidence: 99%
“…This prevents a stable spraying of negative ions, thereby hindering their coupling to HPLC or other separation methods that require a stable operation of ESI for a longer time period. Nanoelectrospray emitters coated with polyaniline, a conductive polymer, were very recently developed and they are resistant to electrical discharge and durable for at least an hour in the negative ion mode [11]. The tips of FortisTips are electrically non-conductive.…”
Section: Capability Of the Emitter For Negative Ion Msmentioning
confidence: 99%
“…However, the negative ion mode is a surprisingly underutilized tool in the analysis of proteins and protein digests. In particular, nanoESI has been shown to analyze oligonucleotides and peptides of low isoelectric point using both metal [21] and polyaniline [22] coated emitters as well as fused silica capillaries [23] and a wire in a pulled capillary [24]. Fewer molecules produce negative ions [25,26] and less salt adduction is observed in the negative ion mode [27], so cleaner mass spectra result.…”
Section: Introductionmentioning
confidence: 97%
“…Fewer molecules produce negative ions [25,26] and less salt adduction is observed in the negative ion mode [27], so cleaner mass spectra result. Data has already been shown that the negative ion mode can produce less interference for peptides than the positive mode [22]. It should be expected then, that by using the negative ion mode, more information and higher quality spectra from protein digests could be obtained.…”
Section: Introductionmentioning
confidence: 98%